Active solar and wind energy potential of urban morphologies on building facades and non-built-up space in between: a case study in Addis Ababa, a Sub-Saharan Africa city - Debebe, Wondwosen; Assefa, Tibebu (Frontiers in Built Environment, 2025)
This article explores into the relationship between urban morphology and renewable energy, specifically focusing on the potential for active solar and wind energy in building facades and non-built-up spaces within blocks in Addis Ababa, a typical Sub-Saharan Africa city. The study involved the analysis of eleven urban blocks representing four different urban morphology typologies selected with geospatial clustering. Solar and wind data are obtained from satellite-based and meteorological sources. Wind and solar analyses are conducted using computational fluid dynamics through Ansys Fluent and Rhino Grasshopper in Ladybug, respectively, with the support of ArcGIS. The findings reveal that the changes in the values of some morphological descriptors have inverse relationship when comparing solar and wind potential on building facades. Conversely, changes in the values of other morphological descriptors generally show a direct relationship independently on solar and wind potential on the non-built up space. It is recommended that the combined effects of solar and wind potential on urban facades be considered based on morphological descriptors. Similarly, the independent effects of solar and wind potential on non-built-up spaces should also be recommended according to these descriptors.